Positioning sustainability to deal with complex systemsː From sustainability identity to sustainability outlook - Genevieve Mortimer; Nina Tura; Bruce Mortimer; Timo Busch (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2019)
In recent decades theoretical frameworks for business sustainability increasingly have encouraged business leaders to engage with their external environments to create positive change. The tacit assumption in these frameworks is that firms demonstrating a high level of sustainability maturity will welcome the inherent complexity of the economic, social and environmental systems as a source of learning and innovation. Still, the question of sustainability leaders' orientation to complexity remains under-researched. Our multi-case study analyzes how business leaders from the Finnish forestry sector, an industry considered to be at a high level of sustainability maturity, align their commitment to sustainability with their approach to complexity. Our findings show that while these managers position sustainability at the center of their discourse about business strategy, their implementation is confined to contexts about which they express the ability to reduce complexity in order to gain a high-level of control. This is an important clarification of a disconnection between sustainability ambition and action. We propose that sustainability maturity be theorized as combining sustainability identity (a firm's identification with the principles of sustainability) and sustainability outlook (business leaders' approach to complex systems). We relate these concepts to propose an enhanced framework for sustainability maturity to assist business leaders to innovate within a complex and unpredictable future.
Keywords: 330; Complex systems; corporate sustainability; sustainability identity; sustainability outlook; sustainability posture